Миллион для бизнеследи: [роман] / Мария Гладкова - Гладкова Мария Вадимовна (ЭКСМО-Пресс, 1999)
Экземпляры: АБ (20180301) / Инвентарный номер: 31391 / Цена: 20.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Г 52 / ББК: 84(2Рос=Рус)6